Reduction. Between the Mind and the Brain - Hieke, Alexander (Publications of the Austrian Ludwig Wittgenstein Society - New Series (N.S.), 2009)
The investigation of the mind has been one of the major concerns of our philosophical tradition and it still is a dominant subject in modern philosophy as well as in science. Many philosophers in the scientific tradition want to solve the "puzzles of the mind". But many philosophers in the very same tradition do regard these puzzles as puzzles of the brain. So, whilst the former think of the mental as something of its own kind, the latter deny that philosophy of mind has to do with anything else but the brain. And then there are those who think that reduction is the way to go: maybe the mental is brain-dependent and hence reducible to the physical, in some way. This volume collects contributions comprising all those points of view, including articles by William Bechtel, Jerry Fodor, Jaegwon Kim, Joëlle Proust and Patrick Suppes.